Comparison of the Successful Outcome of Treatment with Oral Misoprostol with Manual Vacuum Aspiration in First Trimester Incomplete Miscarriage at Tertiary Care Hospital Abbottabad - Arif, Farwah; Moin, Sadaf; Iffet, Shazia; Akram, Ayesha; Nisar, Maryam; Ameen, Sohaila (Indus Journal of Bioscience Research, 2025)
Background: Incomplete miscarriage is a common complication of early pregnancy, requiring prompt and effective management to prevent complications and preserve future fertility. Both oral misoprostol and manual vacuum aspiration are established treatment options, but their comparative efficacy remains debated, making the choice between these modalities crucial for optimal patient care. Objective: To compare the successful outcome of treatment with oral misoprostol with manual vacuum aspiration in first trimester incomplete miscarriage at Tertiary Care Hospital, Abbottabad. Study Design: Randomized controlled trial. Duration and Place of Study: The study was conducted from February to May 2025 at the Department of Gynaecology and Obstetrics, Combined Military Hospital, Abbottabad, following approval of the synopsis. Methodology: This randomized controlled trial included 162 women with first trimester incomplete miscarriage, with 81 participants allocated to each treatment group. Sample size was calculated using OpenEpi software with 95% confidence level and 80% study power, based on previously reported success rates. Group A received oral misoprostol while Group B underwent manual vacuum aspiration. Treatment success was defined as complete evacuation without additional intervention. Results: Manual vacuum aspiration achieved significantly higher success rates compared to oral misoprostol (98.8% vs 82.7%, p<0.001). Mean age was 30.93±5.09 years versus 30.31±5.19 years respectively. Mean gestational age was 9.58±1.70 weeks versus 9.17±1.72 weeks. Conclusion: Manual vacuum aspiration is significantly more effective than oral misoprostol for managing first trimester incomplete miscarriage.